Retrospective Investigation of Cytomegalovirus and Epstein–Barr Virus Positivity in Inflammatory Bowel Disease Patient Biopsies - Hasan Bostancı; Kürşat Dikmen; Ahmet Çağrı Büyükkasap; Sidre Erganis; Kayhan Çağlar; Ayşe Dursun; Gülendam Bozdayı (Gazi Medical Journal)
Objective: Inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are chronic inflammatory conditions affecting the gastrointestinal tract. The aim of this study was to investigate the distribution of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) in the intestinal tissue of patients with IBD. Methods: The study included tissue samples taken from 50 IBD (32 male, 18 female, between the ages of 18-76) patients. Thirty of the patients had CD and 20 had UC. The control group consisted of 31 patients who underwent routine colonoscopy and whose biopsies were extracted from suspicious sites, but no evidence of IBD was found. In these samples, the presence of CMV and EBV viruses was investigated by real-time polymerase chain reaction in our medical virology laboratory. Results: In mucosal tissues, EBV positivity was 50% in UC and 40% in CD; CMV positivity was 35% in UC and 17% in CD. EBV positivity in the control group was 16%, and CMV was not detected. The presence of EBV and CMV in CD (p=0.049; p=0.024) and in UC (p=0.013; p=0.001) patients was statistically significantly higher than that in the control group. We analyzed the differences between the groups in terms of age, clinical features, biopsy locations, surgery type, medical treatment, and biochemical marker results. There was no significant difference in patients with CD compared with the control group. However, there was a statistically significant decrease in albumin and hemoglobin levels in patients with UC compared with the control group. Conclusion: We believe that these viruses may play a role in the pathogenesis of IBD and exacerbation of the disease, and this study shows that patients with IBD undergoing surgery have a high prevalence of EBV and CMV.